Abah in memory (16 August 1943 - 19 September 2022) / Razifa Mohd Razlan - Mohd Razlan, Razifa (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.